Respiratory syncytial virus and human metapneumovirus after allogeneic hematopoietic stem cell transplantation: Impact of the immunodeficiency scoring index, viral load, and ribavirin treatment on the outcomes. Issue 4 (6th April 2020) - Akhmedov, Mobil; Wais, Verena; Sala, Elisa; Neagoie, Adela; Nguyen, Thanh Mai; Gantner, Andrea; von Harsdorf, Stephanie; Kuchenbauer, Florian; Schubert, Axel; Michel, Detlef; Döhner, Hartmut; Bunjes, Donald
Abstract: Introduction: Respiratory viral infections are a major cause of morbidity and mortality among stem cell transplant recipients. While there is a substantial amount of information on prognostic factors and response to ribavirin therapy is available for RSV infections, this information is largely lacking for hMPV. Patients and methods: In total, 71 patients were included in this study: 47 patients with RSV and 24 with hMPV. Forty‐one patients presented as an upper respiratory tract infection (URTI) and 30 as a primary lower respiratory tract infection (LRTI). Patients were stratified as per ISI criteria into low‐, moderate‐, and high‐risk groups. Twenty‐two patients in the URTI cohort received treatment with ribavirin (mainly oral), and 19 patients received no antiviral therapy. The decision for antiviral treatment was at the discretion of the attending physician. All 30 patients with primary LRTI and 10 patients with secondary LRTI were treated with ribavirin, 95% with the intravenous formulation. 45% of these patients received additional treatment with intravenous immunoglobulins. The viral load was assessed indirectly by using the CT value of the RT‐PCR. Results: In the cohort, as whole 11.5% suffered a virus‐associated death, 5% in the URTI group, and 20% in the LRTI group. Sixty‐day mortality was significantly higher in the ISI high‐risk group (log‐rank P  = .05). Mortality was independent of the type of virus ( P  = .817). Respiratory failure with an indication for mechanical ventilation developed in 11.5%, this risk was independent of the type of virus. Progression from URTI to LRTI was observed in 24% of cases with a significantly higher risk (75%) in the ISI high group (log‐rank P  = .001). In the ISI high‐risk group, treatment with ribavirin significantly reduced the risk of progression (log‐rank P  < .001). Neither the type of virus nor the viral load in the nasopharyngeal swab impacted the risk of progression ( P  = .529 and P  = .141, respectively). The detection of co‐pathogens in the BAL fluid was borderline significant for mortality ( P  = .07). Conclusions: We could detect no differences between RSV and hMPV with respect to progression to LRTI, risk of respiratory failure or need for mechanical ventilation and virus‐associated death. The ISI index is of predictive value in hMPV patients with a high ISI score and treatment with oral ribavirin has an equivalent protective effect in RSV and hMPV patients. Treatment of LRTI with intravenous ribavirin results in a similar outcome in RSV‐ and hMPV‐infected patients. We could not detect any benefit of adjunctive treatment with immunoglobulins in both primary and secondary LRTI. No role of viral load as an independent prognostic marker could be detected either for progression to LRTI or death.